Association of FTO Mutations with Risk and Survival of Breast Cancer in a Chinese Population. (4th June 2015) - Zeng, Xianxu; Ban, Zhenying; Cao, Jing; Zhang, Wei; Chu, Tianjiao; Lei, Dongmei; Du, Yanmin
Abstract : Recently, several studies have reported associations between fat mass and obesity-associated (FTO) gene mutations and cancer susceptibility. But little is known about their association with risk and survival of breast cancer in Chinese population. The aim of this study is to examine whether cancer-related FTO polymorphisms are associated with risk and survival of breast cancer and BMI levels in controls in a Chinese population. We genotyped six FTO polymorphisms in a case-control study, including 537 breast cancer cases and 537 controls. FTO rs1477196 AA genotype had significant decreased breast cancer risk [odds ratio (OR) = 0.54, 95% confidence interval (CI): 0.34–0.86] compared to GG genotype, and this association was only found in women with BMI < 24 kg/m 2 (OR = 0.41, 95% CI: 0.22–0.76); and rs16953002 AA genotype conferred significant increased breast cancer risk (OR = 1.80, 95% CI: 1.23–2.63) compared to GG genotype. Haplotype analysis showed that FTO TAC haplotype (rs9939609-rs1477196-rs1121980) had significant reduced breast cancer risk (OR = 0.76, 95% CI: 0.62–0.93) compared with TGC haplotype. But we failed to find any association between FTO polymorphisms and breast cancer survival. These findings suggest that variants in FTO gene may influence breast cancer susceptibility.